A preventive maintenance model for leased equipment subject to internal degradation and external shock damage. (October 2016) - Zhou, Xiaojun; Wu, Changjie; Li, Yanting; Xi, Lifeng
Abstract: A periodic preventive maintenance modeling method is proposed for leased equipment with continuous internal degradation and stochastic external shock damage considered simultaneously, which can facilitate the equipment lessor to optimize the maintenance schedule for the same kind of equipment rented by different lessees. A novel interactive mechanism between the continuous internal degradation and the stochastic external shock damage is established on the hazard rate of the equipment with integrating the imperfect effect of maintenance. Two improvement factors are defined for the modeling of imperfect maintenance. The number of failures resulting from internal degradation and from external shocks are both mathematically deduced based on this interactive mechanism. The optimal preventive maintenance scheme is obtained by minimizing the cumulative maintenance cost throughout the lease period. Numerical example shows that the proposed preventive maintenance model not only can reflect the reliability status of the equipment but also can clearly distinguish between the impact from internal degradation and that from external shocks. Highlights: We propose an imperfect periodic preventive maintenance model for leased equipment. It can distinguish between the impact from internal degradation and that from external shocks. An internal–external interactive mechanism is proposed. Two improvement factors are introduced into the modeling of imperfect maintenance. The model is helpful for the PM scheduling of the same equipment rented by different lessees.